Common Technical Causes of the Failed Rhinoplasty - Davis, Richard E.; Bublik, Michael (Facial Plastic Surgery, 2012)
The adverse rhinoplasty outcome may result from a wide variety of dissimilar causes. Although these causes include psychiatric patient disturbances and severely aberrant wound-healing responses, by far the most common etiology of the failed rhinoplasty is technical failure on behalf of the surgeon. Moreover, a disproportionate number of technical shortcomings stem from errors in basic rhinoplasty technique. Hence, mastery of rhinoplasty fundamentals will prevent a large number of novice errors that often taint the cosmetic outcome. Because many of the remaining technical errors stem from overaggressive tissue removal, tissue-sparing rhinoplasty techniques will also prevent many common causes of technical failure. This article identifies some of the more common technical errors associated with the unsuccessful cosmetic rhinoplasty and also provides insights as to their avoidance.
Keywords: open roof deformity; cephalic trim technique; inverted-V deformity; overresection